Can genomics shed light on the origin of species? - Chris D Jiggins (PLoS Biology, 2019)
Evolutionary biologists are increasingly using population genetic variation across genomes to address questions around the origin and ongoing evolution of species. Patterns of differentiation between closely related species are highly variable across the genome, and a wide variety of processes contribute to that variation. There is an emerging pattern of parallelism, whereby different species pairs in groups of related species show similar differentiation patterns across their genomes, offering an opportunity to test hypotheses regarding the processes underlying species differentiation. A recent study used both simulations and empirical data to investigate different forms of selection in a radiation of monkeyflowers. The parallel patterns emerged very rapidly after divergence and could not be readily explained by selection for removal of deleterious mutations but instead likely results from some combination of adaptive evolution, species incompatibilities, and ongoing gene flow. Overall, an emerging pattern is that there may be a surprising degree of predictability in the genetic architecture of species differences across groups of related species.